INOVASI PEMANFAATAN PUDDING KAPULAGA SEBAGAI POTENSI SUMBER DAYA LOKAL DALAM PENCEGAHAN STUNTING DI DESA PANTAN NANGKA, KECAMATAN LINGE - Sa’ad, Lewaldi; Fajri, Maulidil; Manik, Erni; Khair, Miftahul; Felinda, Putri Lili; Veronica, Cindi; Rahmina, Rahmina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Central Aceh is one of the districts in Aceh province. The capital city of Central Aceh is Takengon, which is a small town with cold weather located on one of the ridges of the Bukit Barisan mountains which lie along the island of Sumatra, Central Aceh district is located in the Gayo highlands. Other districts in this area are Bener Meriah district and Gayo Lues district. The service activities carried out in Kampung Pantan Nangka Village, Linge District, Central Aceh Regency consisted of preparation, socialization and introduction of cardamom pudding products, and training in making cardamom pudding. To get to know pudding, there was socialization and an introduction to the processing of cardamom into pudding, in the form of counseling which was attended by 25 participants. Pudding is one name for various desserts which are generally made from boiled ingredients. In general, pudding is grouped into wet foods which are usually served on certain occasions. Pudding is made from a mixture of gelatin powder, sugar and water. In processing, pudding can be combined with various other ingredients such as fruit, vegetables, milk, nuts, and so on. Pudding has a sweet taste with a soft texture so it is liked by everyone from children